Aplikasi Sistem Informasi Geografis (SIG) Zonasi Kawasan Wilayah Pertambangan Di Kabupaten Madiun Menggunakan Basis Data Spasial - Fajar Rizki Widiatmoko; Yazid Fanani; Donny Rusdian Pratama (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2022)
Madiun Regency is an area that has abundant natural resource potential, one of which is the mining sector. The existing potential is dominated by rock commodities. The potential of rock mining materials, namely; trass, andesite, clay, and backfill. It is necessary to zoning mining areas to optimize the management and utilization of potential resources. Mining area zoning takes into account various land use parameters. The patch method is used as a reference for the weighting and assessment of each parameter using a Geographic Information System (GIS). Zoning can be grouped into Permitted Zones, Conditional Permitted Zones, and Non-permitted Zones. The parameters determining the zoning consist of the distribution of land use based on existing ones as well as spatial and regional planning plans. The results of the identification of potential resources are carried out by analyzing geological maps and obtaining potential resources, among others; sand, sandstone, andesite, trass, clay, and backfill. The results of the zoning of the Madiun Regency mining area are; the area of ​​the zone that can be granted a permit is 37,114.95 ha, the area of ​​the zone that can be granted a conditional permit is 1,090,05 ha, and the area of ​​the zone that cannot be granted a permit is 72,310.35 ha. The results of the zoning of mining areas in the Madiun Regency can be used for consideration of mining land clearing plans based on integrated data.